IMPLEMENTING THE ASSURE MODEL FOR DEVELOPING PAI MEDIA AND TECHNOLOGY AT SMAMDA SIDOARJO - Bilad Tajdidul Islahi; Sunarto (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
This study aims to analyze the implementation of the ASSURE model in the development of Islamic Religious Education (PAI) learning media and technology at SMA Muhammadiyah 2 Sidoarjo. Advancements in information technology require teachers to transition from mere information transmitters to creative instructional designers. The research employs a qualitative descriptive design to explore how teachers utilize the systematic steps of ASSURE—Analyze learners, State objectives, Select methods, Utilize media, Require participation, and Evaluate—to enhance learning. Data were collected through classroom observations, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that the ASSURE model consistently improves learning effectiveness, strengthens teacher-student interaction, and fosters student interest based on Islamic values relevant to modern life. PAI teachers successfully integrate digital technologies such as e-learning and reflective videos with contextual moral values, resulting in an integrative, humanistic, and transformative learning model.